Constructivism in Postmodern Jurisprudence - I. L. Chestnov (Теоретическая и прикладная юриспруденция)
The author of the article shows how they change of the late 20th and early 21st Centuries ideas about reality. Objectivism and naturalism are being replaced by constructivism and mentalism today. What is real in the social world is what is perceived as real and what is constructed by people. This paradigm is becoming dominant not only in sociology, but also in jurisprudence. So, in postclassical criminology, crime and criminality are considered not some objective reality, but the result of the activity of the legislator. However, radical constructivism, which does not take into account external circumstances or structural constraints, cannot be considered an adequate concept. The author formulates an approach that includes both the transcendent foundations of law and the constructivist activity of powerful subjects in the reproduction of law. At the same time, examples from criminology and the opinions of leading scientists from this discipline are given. The necessity of taking into account the historical and socio-cultural context is stated.